2013
DOI: 10.1002/lary.23741
|View full text |Cite
|
Sign up to set email alerts
|

Hearing preservation and speech perception outcomes with electric‐acoustic stimulation after 12 months of listening experience

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 21 publications
0
32
0
1
Order By: Relevance
“…Initial preservation of residual hearing after cochlear implantation can be achieved to varying degrees in 50% to 100% of cases (Lenarz et al 2013; Adunka et al 2013; Huarte & Roland 2014; Usami et al 2014; Gstoettner et al 2009). When residual hearing is preserved, patients may utilize both electric and acoustic hearing in the implanted ear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial preservation of residual hearing after cochlear implantation can be achieved to varying degrees in 50% to 100% of cases (Lenarz et al 2013; Adunka et al 2013; Huarte & Roland 2014; Usami et al 2014; Gstoettner et al 2009). When residual hearing is preserved, patients may utilize both electric and acoustic hearing in the implanted ear.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed post-implantation hearing loss has been reported in 15 to 56% of patients with initially preserved hearing (Gifford et al 2013; Reiss, Turner, Karsten, Erenberg, Taylor & Gantz 2012b; Van Abel et al 2015; Lenarz et al 2013; Adunka et al 2013). In the Hybrid 10 clinical trial, for example, although only 2 out of 87 patients were found to have total hearing loss at the initial one month follow up, an additional 6 patients progressed to total hearing loss between 3 and 24 months after implantation(Gantz et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The EAS and conventional CI cohorts participated in separate, prospective studies [Adunka et al, 2013;Buchman et al, 2014] that included the assessment of quality of life with the APHAB during the 1st year of device use. Demographic information for the UHL cohort is described in the Methods of Experiment I.…”
Section: Subjectsmentioning
confidence: 99%
“…It is assumed that the additional use of drugs such as glucocorticoids during and after implantation stabilize hearing preservation (9). The EAS is now a well-established and efficacious treatment, characterized by increased speech recognition in noise, improved sound quality of music, and more natural hearing (10,11). Because of the improved methods for preservation of the residual hearing, more patients become candidates for EAS surgery (12).…”
mentioning
confidence: 99%